Land Cover Dynamics in Beni Chougrane Mountains, North West of Algeria, Using Remote Sensing - Tayeb Si Tayeb,; Benabdeli Kheloufi, (Journal of Basic & Applied Sciences, 2014)
Land cover change is the result of complex interactions between social and environmental systems, systems that evolve over time. While climate and biophysical phenomena have long been the main drivers of changes in land surfaces, the human is now behind most of the changes affecting terrestrial ecosystems. The main objective of this work is to show the characterization and monitoring of land cover change in semi-arid Mediterranean area. The changes in agro-forest area which is a land use mode in the mountains of Beni-Chougrane at local scale. We used Support Vector Machines method for classification of Landsat TM image, and change detection technique to analyze change of land cover types by comparing the satellite observations of Landsat TM from 1984 to 2009. Our analysis showed that proportion of forest cover decreased from 41% in 1984 to 14% in 2009 that from approximately 190 hectares/year and agriculture land from 18 % to 1.5 %. The results showed that all land cover and lad use area have experienced structural changes in it's globally, Intensive regression of woody natural vegetation imposed by fires and unsustainable use of resources, a remarkable decline in land occupied by agriculture. Suggesting an immediate response to a policy based on priorities for the preservation, protection, development and rational use of land areas.